An Imperfect Algorithm for Coalition Structure Generation - Changder, Narayan; Aknine, Samir; Dutta, Animesh (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
Optimal Coalition Structure Generation (CSG) is a significant research problem that remains difficult to solve. Given n agents, the ODP-IP algorithm (Michalak et al. 2016) achieves the current lowest worst-case time complexity of O(3n). We devise an Imperfect Dynamic Programming (ImDP) algorithm for CSG with runtime O(n2n). Imperfect algorithm means that there are some contrived inputs for which the algorithm fails to give the optimal result. Experimental results confirmed that ImDP algorithm performance is better for several data distribution, and for some it improves dramatically ODP-IP. For example, given 27 agents, with ImDP for agentbased uniform distribution time gain is 91% (i.e. 49 minutes).